DEVELOPMENT OF PAVEMENT CONDITION INDEX MODEL FOR FLEXIBLE PAVEMENT IN BAGHDAD CITY (Journal of Engineering, 2008)
The pavement is one of the basic components of road infrastructure and, therefore, directly influences general levels of transport safety, as well as the quality of transportation services in human and cargo traffic. Accordingly, the objective of the present study is to develop the prediction model for pavement condition index (PCI) for flexible pavement. To achieve this objective, (80) selected pavement sections in four sites in the study area and (1100) sample of pavement sections were selected from these sections for the purpose of (PCI) model building. These data include ; longitudinal , transverse, alligator , slippage and block cracking , rutting ,depression , bleeding , polishing , patching and pothole . The effort to develop a (PCI) model is carried out by using a stepwise regression technique. These statistical processes are carried out with the aid of (STATISTICA – version 5.5) computer package. The validation process for the developed models shows that, this model is adequate to be used for the prediction of pavement condition for flexible pavements within the range of data.